2015
DOI: 10.1111/bju.13020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hexaminolevulinate fluorescence cystoscopy for the diagnosis of non‐muscle‐invasive bladder cancer in daily clinical practice: a Spanish multicentre observational study

Abstract: ObjectiveTo assess the sensitivity and specificity of blue-light cystoscopy (BLC) with hexaminolevulinate as an adjunct to white-light cystoscopy (WLC) vs WLC alone for the detection of non-muscle-invasive bladder cancer (NMIBC), in routine clinical practice in Spain. Patients and MethodAn intra-patient comparative, multicentre, prospective, observational study. Adults with suspected or documented primary or recurrent NMIBC at eight Spanish centres were included in the study. All patients were examined with WL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
(53 reference statements)
2
26
0
Order By: Relevance
“…Thereafter, a fluorescence cystoscopy was accurately performed and any suspicious area was reported on the same map. Biopsies were collected from any suspicious area either under blue or white light and resection of the tumors identified (TUR) [13][14][15][16].Whenever no suspicious areas could be seen, a standard random mapping including 8 biopsies overall was completed. All WLCs and BLCs were performed by the same expert urologist ( Patients with acute or chronic urinary tract infection, urinary tract lithiasis, multi-drug allergies as well as patients underwent recent BCG installation, radiotherapy and multi bladder catheterizations were excluded [12].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, a fluorescence cystoscopy was accurately performed and any suspicious area was reported on the same map. Biopsies were collected from any suspicious area either under blue or white light and resection of the tumors identified (TUR) [13][14][15][16].Whenever no suspicious areas could be seen, a standard random mapping including 8 biopsies overall was completed. All WLCs and BLCs were performed by the same expert urologist ( Patients with acute or chronic urinary tract infection, urinary tract lithiasis, multi-drug allergies as well as patients underwent recent BCG installation, radiotherapy and multi bladder catheterizations were excluded [12].…”
Section: Methodsmentioning
confidence: 99%
“…Among these 33 studies were 10 RCTs of BLC with HAL vs. WLC that were used to meta-analyze sensitivities and specificities. [13][14][15][16][17][18][19][20][21][22] Burger et al recently used raw data of RCTs to metaanalyze recurrence relative risk (RR) for BLC with HAL vs. WLC-assisted TURBT, and this RR (0.761) was used in the baseline decision-tree analysis. 23 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…They found that LVI was associated with time to recurrence and death, while a significant benefit of adjuvant chemotherapy could not be confirmed in a small group of 27 patients with altered p53 expression and LVI. The authors concluded that, although their study did not show a survival benefit for adjuvant chemotherapy in patients with LVI, a possible benefit could not be finally excluded [1].…”
mentioning
confidence: 91%
“…The present prospective study by Palou et al [1], conducted in eight Spanish centres, documents the use of hexaminolevulinate fluorescence cystoscopy (FC)-guided bladder tumour resection and biopsies in 283 patients with non-muscle-invasive bladder cancer (NMIBC). It is an inpatient comparison between white-light cystoscopy and FC.…”
mentioning
confidence: 99%
See 1 more Smart Citation